A rare case of jelly belly (pseudomyxomaperitonnei) - Mokati, Uday Kiran; Barik, Kalandi; Rao, L. Hari Prasada; Vijaya, P.; Avinash, P. (International Surgery Journal, 2017)
Pseudo myxomaperitonnei (PMP) is a rare case with progressive dissemination of mucinous tumours and mucinous ascites in the abdomen and pelvis with an estimated incidence of 1 to 2 out of a million. Psedomyxomaperitonnei is a neoplastic disease originating from a primary mucinous tumor of appendix, mucinous cystadenoma of ovary with a distinctive pattern of the peritoneal spread. Computed tomography and histopathology are the most reliable diagnostic modalities. We present a case of pseudomyxomaperitonnei in a 55 year old male presented with pain abdomen and abdominal distension with ascites. Ultrasonography localized collection noted in right iliac fossa and left iliac fossa and ascites present. Computed tomography showed localized collection noted in right iliac fossa and left iliac fossa which is arising from appendix and ascites present. Exploratory laparotomy peritoneal cavity filled with mucinous substance along with ruptured cyst wall in right iliac fossa was found. The mucinous substance drained and the ruptured cyst was resected with appendix at base. In conclusion, pseudomyxomaperitonnei is a rare presentation. Despite the current standard of treatment modalities as extensive surgical resection combined with chemotherapy, PMP frequently recurs with treatment options being limited at recurrence and with severe impact on quality of life.